Presence of rhlAB, rhlR and rhlR genes in Pseudomonas aeruginosa natives overproductors of ramnolipids - Palomino, Roger A. (2017)
Genes associated to rhamnolipids production were molecularly characterized in 61 bacterial strains from LAMYBIM bacterial collection (Laboratorio de Microbiología y Biotecnología Microbiana, Universidad Nacional Mayor de San Marcos, Perú). Strains were isolated from peruvian environments hydrocarbons polluted and were classified as RL overproducers (n= 21), RL producers (n = 20) and non-producers (n = 20) producers. Molecular identification using the 16S rRNA gene was preceded by the biochemical identification of 61 strains selected with the API 20 NE system. Pseudomonas aeruginosa was the most prevalent strain of the RL overproducers and RL producers. Species such as Burkholderia cepacea, Pseudomonas fluorescens, Aeromonas hydrophila and Chryseobacterium indologenes, were found too. In the same way, non-producers microorganisms were also characterized. The PCR amplification and agarose gel electrophoresis techniques, standarized by the UNAM laboratory, showed that the selected strains had the genes: rhlA, rhlB, rhlR and rhlC. For the sequencing of the rhLABR gene region, four strains were selected: Pseudomonas aeruginosa T2K2, Pseudomonas aeruginosa III T1P2, Pseudomonas aeruginosa 6K-11 and Pseudomonas aeruginosa ATCC 9027, applying the methodology standardized by the UNAM and were compared with Pseudomonas aeruginosa PAO1. Our results show that the genes studied in the selected strains are synonymous with their homologues in Pseudomonas aeruginosa PAO1 standard strain. Therefore, genotypical differences that explain the overproduction of rhamnolipid might be found in other molecular markers not covered in this study.